(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Since March 2020, CORONAVIRUS (COVID-19) pandemic has affected many sectors, including education sector at the global level and at the Kingdom of Saudi Arabia. Preventative procedures have been taken, including suspending teaching and training for K-12 and higher education and moving to use distance education as an alternative to face-to-face education, with the continuation of the Corona pandemic, the Ministry of Education decided to consider the e-learning (distance education and blended education) as a strategic alternative to overcome crises threatening the educational process . With the widespread use of e-learning platforms in the Kingdom of Saudi Arabia, the interest of the quality of e-courses increased more than before. Therefore, this study proposes a model for ensuring the quality of e-learning and e-courses in higher education institutions and developing a set of evidence and suggested performance indicators that help those responsible for quality management to verify and validate the adherence to these standards. Dar Al-Uloom University was chosen as a case study of what was implemented during the Corona pandemic and the extent of the university’s commitment to this standards to ensure continuous improvement and raise the level of performance related to the e-learning system and its e-courses.